Wirtschaftswachstum und Währungsstabilität in Österreich - Hans Zapfe (Kredit und Kapital, 1970)
– Economic Growth and Monetary Stability in Austria The author attempts an appraisal of Austrian economic policy since 1945, applying the criteria of growth and stability, and comes to the conclusion that, from the long-range viewpoint, despite the fact that initially material and organizational reconstruction enjoyed priority these objectives were realized to no less a degree than in other countries. With regard to economic growth, in the fifties Austria kept abreast of the leading western industrial countries. Then came a period of slower growth resulting from the fact that primary and raw material production, which had previously been a prominent growth factor, began to suffer from sales difficulties occasioned by world market conditions and from unfavourable output structures. However, in 1967 and 1968 Austria again held a midfield position among the European industrial countries and in 1969 and 1970 will more likely be among the leaders. The fact that Austria's export figures are very good and that it was possible to achieve those good results even in 1967 when her most important customers were undergoing a recession shows that the mentioned structural difficulties have been successfully overcome. Monetary stability was put on short commons in the first few years of reconstruction. The monetary reform intended to establish equilibrium between money and goods by way of money-absorption measures could only be put into effect step by step owing to the difficulties caused by the fourpower military occupation. Following the stabilization that was completed in 1953 with the declaration of the initial parity to the Monetary Fund, at first a high degree or stability persisted for some years, but this then gave way to a secular depreciation of money, though this trend was no more marked than in most western industrial countries. Austria is in the gratifying position of having squared her balance of payments over a long period and is therefore not bothered with upward or downward revaluation problems. Judged from monetary standpoints, Austria's economic policy has been expedient and has ensured crisis-free settlement of payments with foreign countries coupled with a maximum of liberality. Although there are no convincing and consequentially implemented conceptions, in individual cases obstinate and dificult problems have been solved with effective measures.
Keywords: 330